PH Sai Udayam Management System for PH Sai Udayam Shop - Muthaiah, Sathiswaran; Sulaiman, Rabatul Aduni (Applied Information Technology And Computer Science, 2024)
The PH Sai Udayam Shop, a grocery store acting as a middleman between suppliers and consumers, faced internal challenges in managing its daily operations. To address these issues, a system was developed to streamline the overall functioning of the shop. The system enables administrators to efficiently handle product information, generate reports, and record supplier transactions. For staff members, the system assists in conducting sales activities, generating purchase invoices, and fulfilling online delivery orders. As for customers, they can browse the product list and place delivery orders. The system was created using Visual Studio and PHP, employing a prototype-based methodology and object-oriented approach. Its primary objective is to enhance the management of PH Sai Udayam Shop by organizing operational data and maintaining comprehensive records of shop activities in a database. By leveraging this system, the shop aims to improve efficiency and optimize its operations.